2007
DOI: 10.1097/01.tp.0000268084.64888.f3
|View full text |Cite
|
Sign up to set email alerts
|

Single Bolus Antithymocyte Globulin Versus Basiliximab Induction in Kidney Transplantation With Cyclosporine Triple Immunosuppression: Efficacy and Safety

Abstract: ATG induction significantly reduced DGF. Both induction regimens together with low initial CsA led to significantly less posttransplant dialysis and excellent survival. The high dose ATG was associated with significant hemodynamic and pulmonary side effects during drug infusion.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
72
1

Year Published

2008
2008
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 70 publications
(75 citation statements)
references
References 21 publications
2
72
1
Order By: Relevance
“…However, despite multiple reports demonstrating reasonable safety and possible medical advantages to SD‐rATG induction in renal transplantation, there remains a concern in the transplant community as to the early safety of this approach 9, 10, 13, 18, 19. The present multicenter study was designed to rigorously address these remaining safety concerns using a primary composite end point based on either the physiologic consequences of a severe rATG reaction (fever, hypotension, hypoxia) or the possible severe sequelae (cardiac events and DGF) 20, 21, 22, 23, 24.…”
Section: Discussionmentioning
confidence: 99%
“…However, despite multiple reports demonstrating reasonable safety and possible medical advantages to SD‐rATG induction in renal transplantation, there remains a concern in the transplant community as to the early safety of this approach 9, 10, 13, 18, 19. The present multicenter study was designed to rigorously address these remaining safety concerns using a primary composite end point based on either the physiologic consequences of a severe rATG reaction (fever, hypotension, hypoxia) or the possible severe sequelae (cardiac events and DGF) 20, 21, 22, 23, 24.…”
Section: Discussionmentioning
confidence: 99%
“…[100][101][102][103] The pooled results at 1 year with five studies 98,[100][101][102][103] suggest less BPAR in BAS than PBO or no induction (OR = 0.53; favours BAS; 95% CI 0.40 to 0.70, I 2 = 0.0%, τ 2 = 0.0). Furthermore, Sheashaa et al 99 reported BPAR at 10 years, at which time BAS continues to show a beneficial effect compared with no induction (OR = 0.41, 95% CI 0.18 to 0.96).…”
Section: Adult Randomised Controlled Trial Evidencementioning
confidence: 99%
“…[100][101][102][103] Six studies reported results at 1-year follow-up. [98][99][100][101][102][103] The pooled results at 1 year with five studies 98,[100][101][102][103] suggest no difference between BAS and PBO or no induction: OR = 0.82 (favours BAS; 95% CI 0.56 to 1.21, I 2 = 0.0%, τ 2 = 0.0); 98,[100][101][102][103] one study reported zero events in both arms. 99 …”
Section: Adult Randomised Controlled Trial Evidencementioning
confidence: 99%
See 2 more Smart Citations